Formats, cultural security and China’s going out policy - Keane, Michael; Zhang, J. (Intellect, 2017)
This article looks at the role of format television in the People’s Republic of China. It juxtaposes two key ideas: the ‘one format policy’ and the One Child Policy. Both are government restrictions intended to kerb reproduction. Formats provide a means for the reproduction of programming ideas, that is, they are generative. When formats ‘fit’ cultural understandings they can be remarkably successful, as with family oriented formats. Yet there is something unusual about China: in comparison to many international markets, China offers a unique demographic – those people born after 1978. The article examines a formatted programme called Where Are We Going, Dad? , introduced into China from South Korea, which illustrates a subgenre known as the ‘parent-child caring’ (qinzi) format. The article shows how this genre has capitalised on the interest in the health and future well-being of the One Child in China, as well as spinning off its own formatted offspring.